PERAN AWAM KATOLIK DALAM UPAYA MEMPERJUANGAN HAK MINORITAS DI NEGARA MULTIKULTURAL: (Bentuk Kajian Filosofis Will Kymlicka dan Teologis KGK Art. 899, 1882 dan 2237) - Bei, Dionisius; Pito , Yohanes C.; Endy , Yohanes (Pastoralia Jurnal Penelitian Dosen, 2022)
The focus of writing this paper is to reflect on the role of the Catholic laity in fighting for the rights of the minority in a multicultural country. The participation of Catholic laity is very necessary because by nature they have the right to a proper personal and social life, and the right to worship the God they believe in. However, this right is often ignored by the state because they in certain countries have a minority in their political base, such as in Indonesia. As a consequence, the state, in the name of a democratic system, is more accepting of the demands of the majority in the formation of laws and other public policies. The question is, how do we address this issue? This paper intends to raise Will Kymlicka's philosophical thoughts and theology, as stated in the teachings of the Catechism of the Catholic Church art. 899, 1882 and 2237, as a scalpel for the sake of reflecting on these problems. The goal is that with this study Catholic laypeople get a philosophical basis for the demands of minority rights to the state, so that the state is based on its legacy